O.ÁBDIRAXMANOVTÍŃ SATIRALÍQ SHÍǴARMALARÍNDA OBRAZ JASAW SHEBERLIGI - Seytbekov, A.B. (SCIENCE and SOCIETY, 2025)
The article focuses on the study of O.Abdurahmonov’s skill in creating characters in his satirical works. In particular, the issue of image and character was analyzed based on the writer’s stories.
Keywords: writer; image; drama writer; janre; play; tragedy; stor; epic novel